The New Salmagundi reader : essays, debates, symposia ([Syracuse, NY] : Syracuse Univ. Press, 1996)
These articles, originally published in the American quarterly "Salmagundi" since 1983, provides a record of some of the thinking about a wide range of cultural, political and literary issues.
The Sense of the past -- Homelands -- Writers -- The Art scene -- Criticism -- Intellectuals -- Politics -- Varieties
Salmagundi reader :, The
Keywords: HUMANITIES